2024
DOI: 10.3164/jcbn.23-33
|View full text |Cite
|
Sign up to set email alerts
|

The role of fat indices as factors leading to sarcopenia in older adults residing in underpopulated areas

Yasutaka Mizukami,
Hidenori Onishi,
Yuta Mifuku
et al.

Abstract: Simplifying the diagnostic criteria for sarcopenia is key to establishing effective interventions. Herein, we aimed to clarify novel diagnostic factors. We calculated novel fat indices [total fat index (TFI) and limb fat index (LFI)] and clarified factors leading to pre-sarcopenia and sarcopenia in 594 enrolled older adults. Physical measurements [height, weight, body mass index (BMI), gait speed, grip strength, and skeletal muscle mass] were performed. Sarcopenia was determined using established diagnostic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…(14) Our study reveals that the progression from a healthy condition to pre-sarcopenia in older adults results in a lower limb fat index (LFI), which is a novel fat index. (15) Conversely, LFI became higher in the process of progression from pre-sarcopenia to sarcopenia, revealing that sarcopenia progression is associated with fat. (15) This suggests that fat infiltration into muscles may capture the mechanism that causes muscle inflammation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…(14) Our study reveals that the progression from a healthy condition to pre-sarcopenia in older adults results in a lower limb fat index (LFI), which is a novel fat index. (15) Conversely, LFI became higher in the process of progression from pre-sarcopenia to sarcopenia, revealing that sarcopenia progression is associated with fat. (15) This suggests that fat infiltration into muscles may capture the mechanism that causes muscle inflammation.…”
Section: Resultsmentioning
confidence: 98%
“…(15) Conversely, LFI became higher in the process of progression from pre-sarcopenia to sarcopenia, revealing that sarcopenia progression is associated with fat. (15) This suggests that fat infiltration into muscles may capture the mechanism that causes muscle inflammation. (15) Additionally, this study discovered that the use of body composition analyzers employing the BIA method showed a significant difference in bone mass between the healthy (Normal), Pre-sarcopenia, and Sarcopenia groups in the overall examination and that each group can be separated.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation